1977
DOI: 10.1016/s0022-5347(17)58299-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Stenosis of the Renal Artery Causing Hypertension: Case Report

Abstract: A case is presented of renal artery stenosis causing renin-dependent hypertension 11 1/2 years after irradiation for Wilms tumor. The literature was reviewed briefly for other cases of large artery damage after irradiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…We observed that hypertension was more prevalent among survivors of nonsyndromic, unilateral WT treated with nephrectomy, regardless of radiation status, suggesting that nephrectomy contributes to its pathogenesis. Posttreatment hypertension has been reported previously following abdominal irradiation for WT, 24 including among patients found to have post‐irradiation renal artery stenosis 25‐27 . One large series identified diastolic hypertension at the fifth anniversary after diagnosis of WT among 7% (39/561) of males and 7% (44/610) of females 28 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We observed that hypertension was more prevalent among survivors of nonsyndromic, unilateral WT treated with nephrectomy, regardless of radiation status, suggesting that nephrectomy contributes to its pathogenesis. Posttreatment hypertension has been reported previously following abdominal irradiation for WT, 24 including among patients found to have post‐irradiation renal artery stenosis 25‐27 . One large series identified diastolic hypertension at the fifth anniversary after diagnosis of WT among 7% (39/561) of males and 7% (44/610) of females 28 .…”
Section: Discussionmentioning
confidence: 86%
“…Posttreatment hypertension has been reported previously following abdominal irradiation for WT, 24 including among patients found to have post-irradiation renal artery stenosis. [25][26][27] One large series identified diastolic hypertension at the fifth anniversary after diagnosis of WT among 7% (39/561) of males and 7% (44/610) of females. 28 The hazard ratio for hypertension was The results of this study must be interpreted taking into consideration the limitations related to the small sample size and the study design, which was a nonrandomized sample of the eligible unirradiated and irradiated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional cases of renovascular hypertension associated with abdominal radiotherapy and documented renal artery stenosis have been presented by McGiLl [73], Staab [74], Stanley et a1 [75], and Gerlock [76]. A total of 12 cases are summarized in Tables II and III.…”
Section: Radiation-induced Coronary Artery Diseasementioning
confidence: 98%
“…der Tunica muscularis media durch Kollagen beschrieben. Selten erwähnte Patho- [2,7,11,16,[23][24][25]30]. Dies kann auf einen diagnostischen Bias zurückzuführen sein.…”
Section: Diskussionunclassified
“…Vincristin kann Hypertonie verursachen[31]. Elf[9,11,15,18,20,26,27] der bisher 21 Patienten (Tabelle 1) mit radiogen induzierter Nierenarterienstenose wurden mit Chemotherapie behandelt, lediglich bei vier Patienten[15,20,26,27] wurden die Chemotherapieregime näher bezeichnet. In drei Fallberichten[5,19,34] finden sich keine Angaben zu einer allfälligen Chemotherapie.…”
unclassified